Heat-Treatments Affect Protease Activities and Peptide Profiles of Ruminants' Milk - Leite, Juliana A. S.; Montoya, Carlos A.; Loveday, Simon M.; Maes, Evelyne; Mullaney, Jane A.; McNabb, Warren C.; Roy, Nicole C. (Frontiers in Nutrition, 2021)
Proteases present in milk are heat-sensitive, and their activities increase or decrease depending on the intensity of the thermal treatment applied. The thermal effects on the protease activity are well-known for bovine milk but poorly understood for ovine and caprine milk. This study aimed to determine the nonspecific and specific protease activities in casein and whey fractions isolated from raw bovine, ovine and caprine milk collected in early lactation, and to determine the effects of low-temperature, long-time (63°C for 30 min) and high-temperature, short-time (85°C for 5 min) treatments on protease activities within each milk fraction. The nonspecific protease activities in raw and heat-treated milk samples were determined using the substrate azocasein. Plasmin (the main protease in milk) and plasminogen-derived activities were determined using the chromogenic substrate S-2251 (D-Val-Leu-Lys-pNA dihydrochloride). Peptides were characterized by peptidomics using high-resolution liquid chromatography coupled with tandem mass spectrometry. The activity of all native proteases, shown as nonspecific proteases, was similar between raw bovine and caprine milk samples, but lower than raw ovine milk in the whey fraction. There was no difference between the nonspecific protease activity of the casein fraction of raw bovine and caprine milk samples; both had higher activity than ovine milk. After 63°C/30 min the nonspecific protease activity decreased (44%) for the bovine casein fraction only. In contrast, the protease activity of the milk heated at 85°C/5 min changed depending on the species and fraction. For instance, the activity decreased by 49% for ovine whey fraction, but it increased by 68% for ovine casein fraction. Plasmin and plasminogen were in general inactivated when all milk fractions were heated at 85°C/5 min. Most of the peptides present in heat-treated milk were derived from β-casein and αS1-casein, and they matched the hydrolysis profile of cathepsin D and plasmin. Identified peptides in ruminant milk samples had purported immunomodulatory and inhibitory functions. These findings indicate that the nonspecific protease activity in whey and casein fractions differed between ruminant milk species, and specific thermal treatments could be used to retain better protease activity for all ruminant milk species.